2016
DOI: 10.1210/en.2016-1252
|View full text |Cite
|
Sign up to set email alerts
|

The Hydroxysteroid (17β) Dehydrogenase Family Gene HSD17B12 Is Involved in the Prostaglandin Synthesis Pathway, the Ovarian Function, and Regulation of Fertility

Abstract: The hydroxysteroid (17beta) dehydrogenase (HSD17B)12 gene belongs to the hydroxysteroid (17β) dehydrogenase superfamily, and it has been implicated in the conversion of estrone to estradiol as well as in the synthesis of arachidonic acid (AA). AA is a precursor of prostaglandins, which are involved in the regulation of female reproduction, prompting us to study the role of HSD17B12 enzyme in the ovarian function. We found a broad expression of HSD17B12 enzyme in both human and mouse ovaries. The enzyme was loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 52 publications
1
42
1
1
Order By: Relevance
“…The sections were incubated overnight with one of the primary antibodies at 4 ° C (HSD17B12 [13], ELOVL5 [19], and COX-2 [20][21][22][23]), diluted in 3% bovine serum albumin + 10% normal goat serum in PBST ( Table 2). On the following day, endogenous peroxidase activity was blocked with 3% H 2 O 2 (Sigma-Aldrich, St. Louis, MO, USA) treatment (20 min, room temperature).…”
mentioning
confidence: 99%
“…The sections were incubated overnight with one of the primary antibodies at 4 ° C (HSD17B12 [13], ELOVL5 [19], and COX-2 [20][21][22][23]), diluted in 3% bovine serum albumin + 10% normal goat serum in PBST ( Table 2). On the following day, endogenous peroxidase activity was blocked with 3% H 2 O 2 (Sigma-Aldrich, St. Louis, MO, USA) treatment (20 min, room temperature).…”
mentioning
confidence: 99%
“…In our study, HSD17B12 was enriched for steroid hormone biosynthesis and the expression level of HSD17B12, FSH and LH were decreased after disturbing the expression of lncRNA TCONS_00066406. A previous study has shown that HSD17B12 can effect female reproduction through regulating prostaglandin synthesis [66], which further proved the importance of HSD17B12 in reproduction and prompted the potential role of antisense-interact lncRNA TCONS_00066406 on reproduction. DCBLD2 was recognized as the crucial regulation factor in tumorigenesis [67] and we found it was enriched in growth related pathways, suggesting lncRNA XR_003591760.1 possibly regulates pituitary development by interacting with DCBLD2.…”
Section: Discussionmentioning
confidence: 85%
“…HSD17B1 is mainly expressed in the ovary , and catalyzes lower estrogenic active estrone (E1) to highly active estradiol (E2) (Hakkarainen et al, 2015;Jarvensivu et al, 2015). HSD17B12 has been implicated in the conversion of estrone to estradiol as well as in the synthesis of arachidonic acid (AA), and plays important roles in ovarian function and female fertility (Kemilainen et al, 2016). Accordingly, we propose that the high expression levels of hsd17b1, hsd17b12a and hsd17b 12b in the ovary may be due to its involvement in the maintenance of the ovary, and the degeneration of ovary leads to the downregulation of these genes during the sex reversal grouper.…”
Section: Discussionmentioning
confidence: 99%